The Combination of Phyllanthus niruri, Euphorbia hirta, and Loranthus sp. as a Source of Antioxidant Agents - Kristiani, Elizabeth Betty Elok; Kasmiyati, Sri (Biosaintifika: Journal of Biology & Biology Education, 2021)
Meniran (Phyllanthus niruri), patikan kebo (Euphorbia hirta), and benalu (Loranthus sp.) have often been used by people as medicinal plants. This research aimed to measure the levels of flavonoids, phenolics, and ascorbic acid compounds, as well as the Free Radical Scavenging (FRS) activity of ethyl acetate extract from the mixture of P. niruri, E. hirta, and Loranthus sp. The FRS activity was measured with the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The level of compounds was measured by using the spectrophotometry method with specific reagents. The result of the FRS activity in ethyl acetate extract from the mixture of P. niruri, E. hirta, and Loranthus sp. varied depending on its dose. The measure of FRS in the P. niruri: E. hirta: Loranthus sp 0:0:1 (K-OOL) composition showed a strong result with a value of IC50 97.2 ± 2.1 ppm, while in the 0:0.5:0.5 (K-OEL) composition it was moderate with a value of IC50 147.6 ± 6.5 ppm. The other compositions showed weak and inactive results. The K-OOL composition had the highest flavonoid and phenolic content that were 298.8±0.00 mg QE/g extract and 141.5±2.85 mg GAE/g extract respectively. The composition with the highest ascorbic acid content (298.8±0.00 mg/g extract) was K-OEO composition. So far, research on medicinal plants is still limited to one type of plant. The combination of several types of plants in several formulations allows obtaining a composition that can produce maximum antioxidant capacity. Therefore, this research is expected to produce a combination formulation of various types of medicinal plants that have the K-OOL composition very strong antioxidant activity and can be used as herbal medicines.